Ijtihad dalam Perspektif Ulama ShÃ®âAh Ithnâ Asharîyah - Baharun, Mohammad (ISLAMICA: Jurnal Studi Keislaman, 2007)
For ShÃ®âah Ithna Asyarîyah, ijtihâd (intellectual exercise to extrapolate rulesfrom their sources) is an imperative logical practice. Like Sunnism, this school of thoughtrequires that a mujtahid (the one who exercises ijtihâd) has high intellectual qualificationsand that tight conditions should be applied to him. To this branch of Shiâism, a mujtahidhas a special place and respected status within its social and religious hierarchy. Herepresents the missing imam (Imam Mahdi) whom every one in Shiâism is waiting for hisreturn. With ijtihâd attached to his shoulder, he is considered to be more important as heholds the task of safeguarding and preserving religion.